The contribution of the African Commission on Human and Peoples’ Rights to the promotion and protection of the human rights of lesbian, gay, bisexual and transgender persons in Africa - Teles, Nair Monteiro (University of Pretoria, 2021)
Mini Dissertation (MPhil (Human Rights and Democratisation in Africa))--University of Pretoria, 2021.